Telephone versus face-to-face neuro-oncology consultations: comparing patient satisfaction, convenience, family support and clinician attitude during the COVID-19 pandemic. (15th October 2021) - Toman, Emma; Goddard, Claire; Garratt, William; Berki, Frederick; Sher, Zenab; Scott, Teresa; Stevens, Andrew; Petrik, Vladimir; Ughratdar, Ismail; White, Anwen; Zisakis, Athanasios; Watts, Colin; et al.
Abstract: Aims: During the first wave of the COVID-19 pandemic, to limit the number of patients attending hospital, the neuro-oncology department selected a large number of appointments to be conducted via the telephone. This project aimed to determine how patients and clinicians perceived telephone consultations in the neuro-oncology service compared to traditional face to face appointments. Method: A 20-question patient satisfaction survey combined quantitative and qualitative questions and was distributed between June and August 2020. These were distributed by email to 88 patients who attended neuro-oncology clinic in person ("face-to-face"), or by telephone. Concurrently, a 15-question survey was distributed to all clinicians conducting telephone and face-to-face consultations for the neuro-oncology service. Questions included in the clinician survey were designed to mirror the patient satisfaction questionnaire where possible. Fisher's exact test was used to determine significance, which was set at p< 0.05. Results: 51.1% (n=45) of patients returned the questionnaire. Of those who received telephone appointments, 89.5% (n=17) felt the consultation was convenient, 94.7% (n=18) were satisfied and 80.0% (n=16) were able to have a family member/friend present. Of those who attended face-to-face appointments, 96.0% (n=24) felt their consultation was convenient, 100% (n=25) were satisfied and 87.5% (n=21) were able to have a family member/friend present. There was no significant difference in patient convenience, satisfaction or family/friend presence (p=0.395, p=0.432 and p=0.498 respectively) between face-to-face and telephone clinics. Overall, the clinicians reported undertaking a mean of 9.5 telephone consultations per week. Only 42.8% (n=3) use telephone appointments for first-time neuro-oncology consultations, whereas 100.0% (n=7) use them for results and follow-up appointments. Only 51.7% (n=4) felt that undertaking telephone consultations is convenient and 42.8% (n=3) have experienced difficult situations with patients during telephone consultation. Conclusion: This project suggests that neuro-oncology telephone consultations provide patients with the same level of satisfaction and convenience as face-to-face appointments. We have also demonstrated that using the telephone does not provide a significant barrier to having family or friends present to support the patient. We have shown that clinicians are universally utilising neuro-oncology telephone appointments for follow-up and results whereas much fewer use the telephone for performing initial consultations. Given the high-level of satisfaction demonstrated in the patient questionnaires this reflects effective patient-selection for remote consultations. The COVID-19 pandemic has forced oncology services to evolve and results of this project suggest that telephone neuro-oncology consultations are widely accepted by patients and clinicians. We therefore propose that remote consultations should continue beyond the pandemic in select cases.